2023
DOI: 10.24294/ti.v7.i1.2039
|View full text |Cite
|
Sign up to set email alerts
|

Revolutionizing cancer treatment by boosting dendritic cell vaccine efficacy with graphene oxide

Abstract: Dendritic cells (DCs) are potent antigen presenting cells that play a crucial role in stimulating T cell responses against cancer. DC vaccines have been utilized as an immunotherapy approach for cancer treatment, but their effectiveness is hampered by challenges in the tumor microenvironment. Graphene oxide (GO), a cutting-edge carbon-based nanomaterial, has shown promise in modulating DC activation and function. This review highlights the recent advancements in DC vaccines and explores how GO can enhance thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…The stabilizing properties of graphene-based materials can be tailored and optimized for specific vaccine formulations and target pathogens. The functionalization of the graphene surface with various molecules or coatings can further enhance the stability-improving capabilities of graphene-based components [ 36 , 51 , 52 ].…”
Section: Improved Vaccine Stabilitymentioning
confidence: 99%
“…The stabilizing properties of graphene-based materials can be tailored and optimized for specific vaccine formulations and target pathogens. The functionalization of the graphene surface with various molecules or coatings can further enhance the stability-improving capabilities of graphene-based components [ 36 , 51 , 52 ].…”
Section: Improved Vaccine Stabilitymentioning
confidence: 99%
“…The development of effective DC vaccines has been hampered by various challenges; however, the emergence of nanomaterials, especially graphene oxide (GO), offers promising avenues to enhance the efficacy of DC vaccines. Through a comparative analysis of relevant literature and research, Mohamed et al [7] concluded that the potential of GO and its functionalized derivatives as adjuvants for vaccine formulations is huge because they can enhance vaccine stability, antigen delivery, and immune responses. However, solving several of the above clinical translational challenges requires interdisciplinary collaboration among researchers, clinicians, and regulatory agencies.…”
mentioning
confidence: 99%